(untitled) (Dermatology Reports, 2025)
Scabies, a contagious parasitic skin disease caused by Sarcoptes scabiei, has shown a marked resurgence in several European regions following the COVID-19 pandemic. In Campania, Italy, reported cases increased from 42 in 2020 to 748 in 2024, according to the regional surveillance system (Sistema Premal-UOD). However, the true burden of disease is likely underestimated due to widespread underreporting, delayed diagnosis, and a hidden reservoir of undetected or self-treated cases. This study analyzes epidemiological trends in Campania, highlights limitations in surveillance, and examines the role of pseudo-resistance in treatment failures. The findings underscore the need for robust monitoring, accurate diagnostics, and public health interventions to reduce the ongoing spread of scabies in the region.